Tradisi Kaboro Coi di Desa Sakuru Monta, Bima; Analisis Hukum Islam - Hasan, Hamzah (Universitas Islam Negeri Alauddin Makassar, 2020)
Kaboro Coi practice was originally just a tradition, but the community has considered it an obligation, not carrying out the cooboro coi will get social sanctions from the community, such as being ostracized and the community no longer cares about any event events (hajatan) conducted by families who do not carry out the Kaboro Coi tradition. Seen from the perspective of Islamic law Kaboro coi practice has a substance that shows the value of togetherness, helping each other to help each other, like the concept of